2013
DOI: 10.1111/jsm.12193
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function in Childhood Cancer Survivors: A Report from Project REACH

Abstract: Introduction Of the approximately 12,000 children and adolescents that will be diagnosed with cancer in 2013, it is expected that over 80% of them will become long-term adult survivors of childhood cancer. Although it has been well established that cancer treatment often has profound negative impact on sexual functioning, sexual functioning in adult survivors of childhood cancer is not well understood. Aim The aim of the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
136
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 89 publications
(147 citation statements)
references
References 46 publications
11
136
0
Order By: Relevance
“…Poorer sexual health has been reported among male survivors who had a diagnosis of central nervous system (CNS) tumors compared with those who had other cancer types 9 and among survivors who received treatment during adolescence compared with those who were younger at the time of treatment. 12 The only study that analyzed the association between exposure to cancer therapy and sexual dysfunction did not report an association.7 Previous studies have reported differences in sexual health and its predictive factors between male and female survivors, 3,[7][8][9] indicating that sexual outcomes need to be analyzed within sexes.To better understand the extent and quality of the sexual problems faced by adult male survivors of childhood ALL, we conducted a study on the first large cohort of adult long-term survivors (10 years) of childhood ALL at the Helsinki University Central Hospital. A well validated and comprehensive self-report measure of sexual function was used, and the results were compared with those from an age-matched and sex-matched control group.…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…Poorer sexual health has been reported among male survivors who had a diagnosis of central nervous system (CNS) tumors compared with those who had other cancer types 9 and among survivors who received treatment during adolescence compared with those who were younger at the time of treatment. 12 The only study that analyzed the association between exposure to cancer therapy and sexual dysfunction did not report an association.7 Previous studies have reported differences in sexual health and its predictive factors between male and female survivors, 3,[7][8][9] indicating that sexual outcomes need to be analyzed within sexes.To better understand the extent and quality of the sexual problems faced by adult male survivors of childhood ALL, we conducted a study on the first large cohort of adult long-term survivors (10 years) of childhood ALL at the Helsinki University Central Hospital. A well validated and comprehensive self-report measure of sexual function was used, and the results were compared with those from an age-matched and sex-matched control group.…”
mentioning
confidence: 97%
“…7 Previous studies have reported differences in sexual health and its predictive factors between male and female survivors, 3,[7][8][9] indicating that sexual outcomes need to be analyzed within sexes.…”
Section: 11mentioning
confidence: 99%
See 3 more Smart Citations